Pesticides and bees. (20th December 2013) - Maxim, Laura; Arnold, Gérard
<x xml:space="preserve">Abstract</x> The European Commission's ban on neonicotinoid pesticides in the EU and the resulting lawsuit from Bayer and Syngenta, two major producers, highlights the need for better regulatory guidelines and environmental risk assessment of agricultural pesticides for market approval.<boxed-text content-type="graphic" id="embr201338218-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>